Alih Kode Dan Campur Kode dalam Ceramah Tuan Guru Bajang (TGB) di Media Youtube: Kajian Sosiolinguistik - Baenuri, Ispalola; Nursaly, Baiq Rismarini; Al-Pansori, Muh. Jaelani (LPPM Institut Pendidikan Nusantara Global, 2025)
ABSTRACT This study aims to describe the form of code switching and code mixing in Tuan Guru Bajang's lecture on YouTube media. The method in this study is descriptive qualitative. The data in this study are in the form of words, phrases, or clauses originating from Tuan Guru Bajang's speech which contain linguistic phenomena of code switching and code mixing. The source of this data is in the form of a video of Tuan Guru Bajang's (TGB) lecture on September 15, 2024 which has been selected and determined according to the needs of the researcher. The data collection technique in this study uses tapping techniques and note-taking techniques. The data analysis procedure uses the analysis steps proposed by Miles and Huberman, namely data reduction, data presentation, and drawing conclusions and verification. Based on the results of the data analysis, several uses of code switching and code mixing were found. the use of code switching as many as 6 data, namely 1 internal code switching data and 4 external code switching data. Meanwhile, the use of code mixing was found in 6 data, namely, internal code mixing with the insertion of elements in the form of words 3 data, external code mixing based on the insertion of words 1 data, code mixing based on the insertion of phrases 1 data, and mixed code mixing as many as 2 data.